Ophelia transformed: revisioning Shakespeare’s Hamlet - Mohammad Safaei,; Ruzy Suliza Hashim, (Penerbit UKM, 2013)
The critical literature on Ophelia has been constrained to the scope of her characterization within Hamlet and to the corpus of literary criticism that has drawn upon the Shakespearean play to portray the contours of her personality. She is often regarded as the mirror of fragility and frustration; she is lascivious and prone to promiscuity; she has no significance in the structural design of the Shakespeare‟s play except to serve as an object of pleasure for Hamlet. Despite all this, Ophelia, within the domain of revisioning literature, has obtained new dimensions which stand in stark contradiction to her traditional figure. This article intends to address the new aspects of her character within the scope of three twenty-first century novels, namely Ophelia, The Prince of Denmark, and The Dead Fathers Club, which have transformed the Shakespearean play. Though Ophelia‟s sensuality is emphasized in all these novels, she is endowed with agency, voice, and a skeptical cast of mind. She is defiant of patriarchal and divine authority; and she at times serves as a haven for the young Hamlet. It is argued that these new dimensions of Ophelia‟s characterization should be construed not only as a response to the Shakespearean text but as a reaction to the bulk of literature which has yielded to the predominantly male-oriented readings of Ophelia.